Implikasi Pendekatan Multipple Intelligences Menurut Gardner Bagi Pembelajaran Pendidikan Agama Islam (PAI) - Muhamad Ansori (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
This research describes the theory of multiple intelligence and its implication for Is lame education. Result of this research is expected can reply a little from so much pro blems of Islamic education. Problems which can be witnessed, namely religion study during the time not yet full develop various potencies or multi of intellegence. Others, Islam taught by more though Islam of full of value and norm which must be practiced. Result of research indicate that the that intellegence potency is not single but majemuk (multiple intellegence), even altogether can be brought back to three elementary intellegence type: IQ, El, and IS. Thereby, related! relevant of multi intellegence with the study development lay in deduction to study which only develop the cognate aspect neglectfully aspect of affective andpsychemotor Keyword : Pendekatan Multipple Intelligences Gardner, Pembelajaran PAI